A dynamical process-based model for quantifying global agricultural ammonia emissions – AMmonia–CLIMate v1.0 (AMCLIM v1.0) – Part 2: Livestock farming - J. Jiang; J. Jiang; J. Jiang; D. S. Stevenson; A. Uwizeye; G. Tempio; A. Falcucci; F. Casu; M. A. Sutton (Geoscientific Model Development)
Agricultural ammonia (NH3) emissions are a major pathway of nitrogen loss, which can have significant environmental consequences, such as air and water pollution, ecosystem damage, and biodiversity loss. Ammonia emissions related to livestock farming are major sources in the agricultural sector, resulting from animal housing, manure management and land application. This paper is the second part of the description of the AMmonia–CLIMate (AMCLIM) model, presenting the development and application of all three main modules to estimate NH3 emissions from livestock, including pigs, poultry (chickens), cattle, sheep and goats. The AMCLIM model simulates the flows of N species at different stages of livestock agriculture. It incorporates the effects of environmental factors and also provides an adequate level of detail for the representation of human management practices. According to simulations by AMCLIM, it is estimated that NH3 emissions from global livestock farming are about 29.9 Tg N yr−1, accounting for around 30 % of total excreted nitrogen. Cattle and buffalo systems are estimated to be the largest sources of NH3 emissions, contributing over 60 % of total livestock emissions. Both pig and poultry systems result in more than 15 % of estimated total emissions, while sheep and goats are responsible for the remaining 7 %. High volatilization rates frequently occur in hot regions, indicating the climate-dependence of NH3 volatilization. It is also shown how AMCLIM can simulate the influence of management practices on NH3 volatilization, e.g. illustrating how fully enclosed animal houses with heating and forced ventilation can result in higher emissions than naturally ventilated barns, while poorly managed manure leads to substantially increased NH3 emissions.